2021
DOI: 10.18203/issn.2455-4529.intjresdermatol20211427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical effectiveness and safety of super bioavailable itraconazole and conventional itraconazole in management of dermatophytosis: a retrospective data analysis

Abstract: <p class="abstract"><strong>Background:</strong> A newer itraconazole formulation i.e., super bioavailable itraconazole has been launched recently in India which is claimed to overcome all the pharmacokinetic challenges faced with conventional itraconazole. The present retrospective data analysis was undertaken to evaluate the effectiveness and safety of super bioavailable itraconazole in comparison with conventional itraconazole in the treatment of dermatophytosis in Indian patients.</p&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In a retrospective study by Mahajan et al published in 2021, 56% of the patients achieved complete clearance of their symptoms in the SBITZ group, whereas 34% achieved the same in the CITZ group (p<0.05). 15 From their results, the authors concluded that SBITZ was more effective than CITZ, with a similar safety profile, in the treatment of dermatophytosis. In addition, a retrospective cohort study by Ghate et al on SBITZ concluded that patients treated with SBITZ showed greater improvement in the clearance of symptoms as well as lesions in just 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study by Mahajan et al published in 2021, 56% of the patients achieved complete clearance of their symptoms in the SBITZ group, whereas 34% achieved the same in the CITZ group (p<0.05). 15 From their results, the authors concluded that SBITZ was more effective than CITZ, with a similar safety profile, in the treatment of dermatophytosis. In addition, a retrospective cohort study by Ghate et al on SBITZ concluded that patients treated with SBITZ showed greater improvement in the clearance of symptoms as well as lesions in just 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, majority of the patients were males, similar to as reported in previous studies in patients with superficial dermatophytic infection. [20][21][22] The low incidence of dermatophytic infections in females could be attributed to the comparatively low reporting of female patients to hospitals due to the social stigma, especially in the rural areas of our country. 23 However, isolated reports have also shown contrasting results with female prepondrance as seen in a study by Das and colleagues in India.…”
Section: Discussionmentioning
confidence: 99%
“…13,20,[26][27][28] Several previous studies have reported a higher effectiveness with SB-itraconazole versus the conventional itraconazole for the treatment of superficial dermatophytic infections. 17,20,22,29 Shenoy et al compared the efficacy and safety of SB-itraconazole (n=26) versus conventional itraconazole (n=33) in an open-label, randomized, double-arm clinical trial. In patients receiving SB-itraconazole, a clinical cure was reported within 4 weeks in about 65.38% of the patients including the naïve as well as recalcitrant cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The desired sample size of 87 patients in each group was calculated considering 90% power to reject the null hypothesis of zero effect size, with a population effect size of 0.53, 15 the significance level (alpha) was 0.05, using a two-sided z-test with a dropout rate of 15%.…”
Section: Methodsmentioning
confidence: 99%